Novel alkylaminophenols as antibacterial agents against Staphylococcus aureus infections - Alves, Bárbara André (2022)
Bone and implant-related infections caused by Staphylococcus aureus, including methicillin-resistant strains, remains one of the main concerns in modern orthopedic surgery being considered a significant cause of morbidity and mortality worldwide. The rapid increase of S. aureus antimicrobial resistance together with their impact in healthcare, highlights the urgent need of alternative therapeutic compounds. We have recently demonstrated that novel alkylaminophenols (NiPharmins) are promising effective antibacterial agents against several multi-resistant Gram-positive bacteria, including S. aureus. Herein, we evaluated the ability of NiPharmins to induce antimicrobial resistance, its antibiofilm capacity, and the antimicrobial activity of NiPharmin-derived mesoporous silica nanoparticles (MSNs). S. aureus isogenic clones were continuously propagated in vitro without and under a NiPharmin and rifampicin (proof-of-concept) sub-inhibitory concentrations (MIC). Phenotypic tests, coupled with whole genome sequencing were used to assess the putative acquisition of resistance. Regarding antibiofilm capacity, the MIC and biomass of the biofilm was determined. The antimicrobial activity of NiPharmin derivatives was also evaluated. For NiPharmin, the MIC remained unchanged (0.488 μg/mL) during the whole assay, confirmed by comparative genomic analysis between isogenic clones propagated under pressure versus the original isogenic clone, where no resistance-associated mutations were found. This behavior highly contrasts with rifampicin, for which resistant clones started to appear soon after the 2nd passage, reaching MICs up to 4000-fold higher for some clones at the end of the assay. Multiple mutations were observed on the rpoB gene, which are known to be associated to differential susceptibilities to rifampicin. NiPharmin has apparently no preventive activity against biofilms and lost its antibacterial activity when equipped with a triazole-derived linker, prone for MSN grafting. Overall, the strong antimicrobial activity of NiPharmin together with its low toxicity and apparent lack of potential to induce antimicrobial resistance makes this compound a promising therapeutic alternative for the prevention of S. aureus infections.